2006
DOI: 10.1097/01.inf.0000226842.23106.a2
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in the Diagnosis of Enteroviral Infection in Young Children

Abstract: The use of stool cultures to identify asymptomatic enteroviral infections in infants in an NICU can be fraught with problems because of high frequency of C. difficile toxin and the nonspecific toxic effects of stool on tissue culture cells. These problems can be rectified when proper procedures are followed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 13 publications
2
11
2
Order By: Relevance
“…Accordingly, 15.8% of the culturing‐positive samples were identified with a given serotype. Similar results were presented by Faden et al [2006], when only one of 31 culturing‐positive samples was confirmed positive. The methods used by Faden et al [2006] differ partly from ours but the difficulties in the identification may be the same.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Accordingly, 15.8% of the culturing‐positive samples were identified with a given serotype. Similar results were presented by Faden et al [2006], when only one of 31 culturing‐positive samples was confirmed positive. The methods used by Faden et al [2006] differ partly from ours but the difficulties in the identification may be the same.…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were presented by Faden et al [2006], when only one of 31 culturing‐positive samples was confirmed positive. The methods used by Faden et al [2006] differ partly from ours but the difficulties in the identification may be the same. There are toxic compounds, for example toxin produced by Clostridium difficile , in stool which can cause effect similar to enterovirus CPE [Schmidt et al, 1980; Faden et al, 2006].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Overall, 16.6% (53/320) of the stool samples tested positive using real-time PCR, and the serotypes were identified in 10.6% (34/320) of the total number of samples. This result is higher than in recent reports [13], [14], wherein only 4.8% of the specimens were HEV-positive in Swedish samples. In this study, 21 different enterovirus serotypes were detected, which suggests that enteroviral infections occur primarily in the Asia-Pacific region, and that the combination of cell lines, real-time PCR, and RT-snPCR is more efficient and accurate than traditional PCR that only uses primers 222 and 292.…”
Section: Discussioncontrasting
confidence: 74%
“…However, the cross-reaction of antibodies to quickly degenerating RD cells was mistaken for positive staining. Faden et al (2006) also had a similar problem with the quickly degenerating cell line A549. The WHO recommends establishing conditions (adjustment of cell count and concentration of fetal calf serum) that will allow cells to last for at least 5-7 days without degeneration (WHO, 2004).…”
Section: Choice Of Cell Linesmentioning
confidence: 99%